2020
DOI: 10.1111/jsr.13179
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing in patients with stroke‐induced dysphagia

Abstract: This study examined the nature and characteristics of sleep-disordered breathing, including obstructive sleep apnea and central sleep apnea, in patients with post-stroke dysphagia, to determine the demographic, anthropometric and clinical variables that were associated with sleep-disordered breathing. Thirty-nine patients diagnosed with acute stroke (28 males and 11 females with a mean age of 72.3 ± 10.0 years) underwent overnight polysomnography (within 3.9 ± 1.6 days after admission). Sleep-disordered breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…However, in the stable stage of stroke, this type of apnea decreases significantly, which coincides with the recovery of pharyngeal muscle function 10. The current study showed that the severity of dysphagia is related to the severity of obstructive sleep apnea 11. In addition, laryngopharyngeal paralysis can easily cause aspiration,12,13 which increased the risk of pneumonia by 3 to 5 times 14,15.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, in the stable stage of stroke, this type of apnea decreases significantly, which coincides with the recovery of pharyngeal muscle function 10. The current study showed that the severity of dysphagia is related to the severity of obstructive sleep apnea 11. In addition, laryngopharyngeal paralysis can easily cause aspiration,12,13 which increased the risk of pneumonia by 3 to 5 times 14,15.…”
Section: Discussionsupporting
confidence: 52%
“…10 The current study showed that the severity of dysphagia is related to the severity of obstructive sleep apnea. 11 In addition, laryngopharyngeal paralysis can easily cause aspiration, 12,13 which increased the risk of pneumonia by 3 to 5 times. 14,15 These 2 kinds of complications can cause hypoxemia, indirectly aggravate the intracranial ischemic injury, and also aggravate the central dysfunction of visceral activities.…”
Section: Dysphagia After MI May Lead To Hypoxia and Aggravate Intracr...mentioning
confidence: 99%
“…In this view, OSA+ patients are at higher risk to develop complications related to dysphagia, in particular aspiration pneumonia. Interestingly, dysphagia is often reversible within a few weeks after stroke, due to gradual recovery of pharyngeal muscle function [ 43 , 44 ]. Therefore, the sleep-disordered breathing observed in AIS may improve simultaneously with the recovery of dysphagia [ 16 , 22 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though several studies failed to demonstrate a direct correlation among stroke topography and SDB [43], strokes involving the central respiratory pattern generator can induce respiratory instability and, in turn, promote both central and obstructive SDB [36, 42•]. In the acute stroke, several factors compromise the patency of the upper airways, such as a weakness or incoordination of the pharyngeal [44,45], intercostal and diaphragmatic muscles [46], increased rostral fluid shift [47], and prolonged supine position [48]. Moreover, a reduced arousal response may concur to increase the length of apnea and the hypoxic burden.…”
Section: Sleep Apnea In Stroke Patients: New Onset or Pre-existing Co...mentioning
confidence: 99%